Social work and social welfare : an invitation - Berg-Weger, Marla , 1956- (New directions in social work (Boston, Mass.), 2010)
Introduces students to the knowledge, skills, and values that are essential for working with individuals, families, groups, organizations, and communities in various practice settings. This title features demographic, statistical, legislative, policy, and research information, and sensitive discussions of contemporary ethical issues